Pure Thalamic Infarct: 8-Year Follow-Up Study in a Hospital in China - Liang, He; Sarma, Anand Karthik; Wang, Zhenxing; Mo, Ming; Lin, Jianwen; Ji, Xunming; Chen, Dong; Liu, Yi (Frontiers in Neurology, 2021)
Pure thalamic infarct is a rare lacunar stroke type, with little known about long-term outcomes. This 8-year, single-center, retrospective study evaluated the clinical background, etiology, Trial of ORG 10172 in Acute Stroke Treatment (TOAST) classification, and 8-year follow-up results in 27 patients with pure thalamic infarcts identified by MR diffusion-weighted imaging in Dalian, China. All patients presented chief complaints of limb weakness or sensory disturbances. Hypertension (24/27, 88.9%), diabetes (12/27, 44.4%), atrial fibrillation (1/27, 3.7%), hyperlipidemia (10/27, 37%), hyperhomocysteinemia (6/27, 22.2%), smoking history (10/27, 37%; 9/15, 60% for men; 1/12, 8.3% for women), and excessive alcohol consumption history (7/27, 25.9%; 7/15, 46.7% for men; 0 for women) were observed in our patient population. Based on TOAST classification, 1 patient had large artery atherosclerosis (7.14%), 23 had small vessel occlusion (SVO; 85.2%), and 3 patients were unidentified due to lack of cerebral angiography. The thalamic blood supply classification were as follows: 23 (85.2%), inferolateral territory; 1 (3.7%), tuberothalamic territory; 2 (7.4%), combination of tuberothalamic and paramedian arteries; 1 (3.7%), combination of inferolateral and paramedian arteries; 0, posterior choroidal arteries. During the 8-year follow-up, 3 patients died of colon cancer, multi-organ failure, and kidney failure, respectively; 7 presented with a recurrent stroke; while 10 recovered well with their risk factors under control. In conclusion, our cohort of pure thalamic infarcts were mainly due to SVO (TOAST), with hypertension as the main risk factor, and the inferolateral artery as the most implicated arterial territory. Less severe outcome or stroke recurrence are identified in long-term follow-up of pure thalamic infarcts. Other comorbidities would be cause of death in aged patients.